Visceral organ growth patterns in Saanen goats - Andrade, M. E.B. [UNESP]; Härter, C. J.; Gindri, M. [UNESP]; Resende, K. T. [UNESP]; Teixeira, I. A.M.A. [UNESP] (Cambridge University Press (CUP), 2019)
Visceral organs play an important role in animals' energy requirements, so their growth must be well understood. The objective of the current study was to fit and compare growth curves that best describe body and visceral organ growth over time in Saanen goats of different sexes. Data were synthesized from seven studies in which curves were fitted to visceral organ growth over time for female, intact male and castrated male Saanen goats from 5 to 45 kg body weight. The liver, pancreas, spleen, rumen-reticulum, omasum, abomasum, small intestine, large intestine and mesenteric adipose tissue (MAT) data were fitted to eight models: Simple linear regression, quadratic, monomolecular, Brody, Von Bertalanffy, logistic, Gompertz and Richards. The best-fit model was chosen based on the corrected Akaike information criterion and the concordance correlation coefficient. Model parameters for each sex were compared. Overall, the model that best described visceral organ growth was the logistic model. Sex did not influence the parameters that predicted organ growth (g), except for MAT, where females presented a lower tissue deposition rate and greater inflection point than males. Irrespective of sex, at the beginning of the growth curve, the liver accounted for 28 ± 1.1 g/kg of empty body weight, and the inflection point occurred at 1.7 months. The rumen-reticulum and large intestine presented higher growth rates in the first 2 months of life. Knowledge of the visceral organ growth curve is useful in improving the understanding of the effect of nutritional requirements for goats and must be used to optimize the nutritional plans.
Keywords: Energy requirements; gastrointestinal tract; sex effects